Advances and Applications of Nano-antimicrobial Treatments (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Nowadays, great concerns are associated with the resistance demonstrated by many microorganisms towards the conventional antibiotic therapies. The failure of traditional antimicrobials, and the increasing healthcare costs, have encouraged scientific research and the development of novel antimicrobial agents. Particularly, there is a great deal of interest in nanotechnologies and in antibacterial products obtained through the incorporation of antibacterial agents or the deposition of antibacterial coatings for prevention of biofilm-associated infections. The main focus of the forthcoming Special Issue is, therefore, to present the most recent efforts in scientific research in the development of advanced antimicrobial materials, with special attention to nature-inspired antimicrobial agents and antimicrobials nanomaterials and nanocoatings. For this purpose, we intend to collect original research articles and reviews on the synthesis and characterization of antimicrobial agents, as well as on the development of antimicrobial products for different applications.